STRATEGI PENGEMBANGAN USAHATANI JAMUR TIRAM DI KECAMATAN BATURAJA TIMUR KABUPATEN OGAN KOMERING ULU (JASEP, 2019)
This study aims to determine the development strategy of oyster mushroom farming in East Baturaja District, OKU Regency. Data collection method used is to collect primary and secondary data. The data is processed and analyzed using SWOT matrix analysis, by identifying internal and external factors so that a grand strategy is developed in developing oyster mushroom farming, namely by keeping oyster mushroom production high, maximizing land function, increasing production capacity by creating its own baglog, following training / training, as much as possible using vegetable pesticides is more concerned with the quality of oyster mushroom production by implementing appropriate integrated pest control.